Fine-tuning of a nanostructure, swelling, and drug delivery profile by blending ureasil-PEO and ureasil-PPO hybrids - Molina, Eduardo F. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Briois, Valerie; Santilli, Celso Valentim [UNESP] (Royal Soc Chemistry, 2014)
Urea-cross-linked polyether-siloxane hybrid blends with tuneable hydrophilic/hydrophobic features were prepared from a mixture of poly(ethylene oxide) (PEO1900) and poly(propylene oxide) (PPO2000), hybridized by end-chain functionalization with (3-isocyanatopropyl)triethoxysilane. The aim of this study was to demonstrate that combination of different polymer phases produces materials with hydrophilic and hydrophobic domains. Swellability and the drug release profile could be easily tuned by varying the ureasil-PEO/ureasil-PPO ratio in the hybrid matrix. Differential scanning calorimetry (DSC) and small-angle X-ray scattering (SAXS) analyses indicated that the nanostructure of the hybrid blends could be described by the existence of a homogeneous mixture of PEO1900 and PPO2000 in the hybrid network, with a fraction of lamellar domains being derived from the PEO1900 crystallinity. A correlation between the nanoscopic features and the kinetics of the swelling mechanism is proposed, based on the results of in situ SAXS analyses. In situ UV-vis spectroscopy monitoring indicated that the kinetics of drug release from the PEO1900-PPO2000 hybrid blends could be controlled by varying the proportions of the hydrophilic (PEO) and hydrophobic (PPO) molecules.